Derivation of Phase 3 dosing for peginterferon lambda‐1a in chronic hepatitis C, Part 1: Modeling optimal treatment duration and sustained virologic response rates. (24th July 2014) - Wang, Xiaodong; Hruska, Matthew; Chan, Phyllis; Ahmad, Alaa; Freeman, Jeremy; Horga, Maria Arantxa; Hillson, Jan; Kansra, Vikram; Lopez‐Talavera, Juan‐Carlos
Abstract Peginterferon lambda‐1a (Lambda) is under clinical development for the treatment of chronic hepatitis B and C virus (HBV, HCV, respectively) infection. This is the first of two manuscripts detailing the pharmacodynamic derivation of Lambda dosing and treatment durations for Phase 3 studies in HCV, based on Phase 2 data. We describe here the derivation of a population model of Lambda exposure; the adaptation of a previously published viral dynamic model for Lambda treatment and host genotype, and its use to simulate sustained virologic responses (SVR). Lambda population pharmacokinetics was described by a one‐compartment model with first‐order absorption, and 33.0 L per day clearance with 47% interindividual (36% intra‐individual) variability. Weight explained a negligible proportion of the variability. Based on SVR predictions, optimum treatment durations were 48 weeks for HCV genotypes 1 or 4 (SVR estimates for 120, 180, and 240 μg Lambda: 58%, 54%, 47%, respectively) and 24 weeks for genotypes 2 or 3 (75%, 72%, 67%). SVR predictions for 240 μg were lower due to dropout predictions. The SVR model established the optimum treatment duration for Phase 3 studies but did not differentiate between 120 and 180 μg dosing. A companion manuscript describes dose selection based on exposure–response/safety modeling.